2017
DOI: 10.1002/14651858.cd012057.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for neuropathic pain in adults

Abstract: Due to the limited data available, there is insufficient evidence to support or refute the use of acupuncture for neuropathic pain in general, or for any specific neuropathic pain condition when compared with sham acupuncture or other active therapies. Five studies are still ongoing and seven studies are awaiting classification due to the unclear treatment duration, and the results of these studies may influence the current findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 111 publications
1
59
0
2
Order By: Relevance
“…Chinese medical formulations such as aconitum may improve neuropathic pain, but overall there is little evidence to support the use of traditional Chinese medicine for neuropathic pain [ 17 ]. A recent Cochrane review concluded that there is currently insufficient evidence to support or refute the use of acupuncture for neuropathic pain [ 18 ]. Despite the lack of supporting evidence, the popularity of traditional Chinese medicine for chronic NP observed here may be due to cultural influences and the difficulty in effectively reducing neuropathic pain with conventional treatment [ 1 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chinese medical formulations such as aconitum may improve neuropathic pain, but overall there is little evidence to support the use of traditional Chinese medicine for neuropathic pain [ 17 ]. A recent Cochrane review concluded that there is currently insufficient evidence to support or refute the use of acupuncture for neuropathic pain [ 18 ]. Despite the lack of supporting evidence, the popularity of traditional Chinese medicine for chronic NP observed here may be due to cultural influences and the difficulty in effectively reducing neuropathic pain with conventional treatment [ 1 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…High PDQ scores are frequent in patients with FMS, and in these patients, high PDQ is probably a measure of pain centralization rather than an expression of injury to the somatosensory system [30][31][32]. In any case, neuropathic pain features are classically difficult manifestations to treat, both pharmacologically and with acupuncture [33]. is study has shown that through acupuncture, sensations that evoke the presence of neuropathic pain undergo a significant improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is considered to be one of the most popular complementary interventions and it is increasingly used for treatment of chronic pain. However, the Cochrane review of Ju et al (Ju et al, 2017) about benefits and harms of acupuncture for neuropathic pain indicated that currently available evidence shows no clear difference between acupuncture treatment and tested comparators among adults with chronic neuropathic pain. Difference in pain intensity between manual acupuncture and sham acupuncture was minimal and based on one study only.…”
Section: What Are the Implications Of The Cochrane Evidence For Practmentioning
confidence: 99%
“…For this reason, healthcare workers in the field of rehabilitation should be familiar with the current evidence about benefits and harms of acupuncture for various conditions. A Cochrane review addresses analgesic efficacy as well as safety of acupuncture for chronic neuropathic pain in adults (Ju et al, 2017):…”
Section: Introductionmentioning
confidence: 99%